Dietary diversity, sociality, and the evolution of ant gustation - Smith, E. Jordan; Vizueta, Joel; Younger, Meg A.; Mullen, Sean P.; Traniello, James F. A. (Frontiers in Ecology and Evolution, 2023)
Ants have remarkably diverse diets and extraordinary species richness, making them an excellent model system to study the evolution of taste. In this entirely eusocial clade, food choice and the mechanisms that regulate feeding have both individual and social dimensions. How taste receptors and sensory processing drive food preferences to generate dietary breadth in ants is poorly understood. It is additionally unclear how elements of colony organization such as division of labor and social food flow impact the mechanistic basis and evolution of taste. Previous work on dipteran, lepidopteran, and hymenopteran gustatory systems, while foundational, provide limited insights into ant dietary specialization. Here we synthesize and analyze research on ant gustation to identify mechanisms, sociobiological correlates, and phylogenetic patterns. We discuss the current state of genomic analyses of taste and future research. We propose that strikingly polymorphic species of Pheidole, Cephalotes, Camponotus, and leafcutter ants (Atta and Acromyrmex) offer compelling social systems to explore adaptive variation in gustation because of their pronounced division of labor in which morphologically, behaviorally, and neurally differentiated workers vary in feeding behavior. Research on ant gustation within and among species will advance our understanding of sensory systems and provide insight into the impact of taste on the evolution of species diversity and how social organization influences gustation.